Heparins: A Shift of Paradigm - Hemker, H. Coenraad; Al Dieri, Raed; Béguin, Suzette (Frontiers in Medicine, 2019)
Heparins inhibit the thrombin forming capacity of plasma, i.e. the endogenous thrombin potential (ETP), by their anti-thrombin (aIIa) activity, the anti-factor Xa (aXa) activity is of minimal importance. This holds for both unfractionated heparin (UFH) and low molecular weight (LMWH) heparin at aXa/aIIa ratios < 25. Clinical experience and epidemiological evidence show that there is a direct relationship between the ETP and the risk of thrombosis and bleeding. Consequently the therapeutic potency of a heparin is determined by the concentration of the moiety with aIIa activity, i.e. of a domain in which 12 sugar flank the high affinity antithrombin-binding pentasaccharide (HA5) at one side. The response of individual plasmas to a fixed dose of any heparin is highly variable. This suggests that individualisation of heparin dosage, on basis of the ETP, might reduce bleeding or re-thrombosis. There exist simple laboratory methods for both the ETP and the concentration of C-domain. These methods can be used both for unequivocally characterisation of a heparin preparation and for controlling heparin therapy and allow arbitrary units relative to a standard to be abandoned. These tests are not yet routinely available, however, which severely encumbers progress in the field.